The Effect of Hydrocotyle sibthorpioides Lam. Extracts on in Vitro Dengue Replication - Fitrien, Husin; Yean, Yean Chan; Siew Hua, Gan; Siti Amrah, Sulaiman; Rafidah Hanim, Shueb (Hindawi Publishing Corporation, 2015)
Objective. To investigate the potential effect of Hydrocotyle sibthorpioides Lam. (H. sibthorpioides) extracts against in vitro dengue viral replication. Methods. The cytotoxicity of H. sibthorpioides was evaluated using a cell viability assay. Cells were pre- and posttreated with water and methanol extracts of H. sibthorpioides, and the viral inhibitory effect was investigated by observing the morphological changes, which were further confirmed by plaque assay. Results. The methanolic extract cytotoxicity was higher in Vero and C6/36 cells than the cytotoxicity of the water extract. Preincubation of the cells with H. sibthorpioides extract showed nonexistent to mild prophylactic effects. The posttreatment of Vero cells with H. sibthorpioides methanolic extract presented higher antidengue activities when compared with the water extract. Surprisingly, posttreatment of C6/36 cells resulted in an enhancement of viral replication. Conclusion. H. sibthorpioides had variable effects on dengue viral replication, depending on the treatment, cell lines, and solvent types. This study provides important novel insights on the phytomedicinal properties of H. sibthorpioides extracts on dengue virus.